(untitled) (Czech Journal of International Relations, 1997)
The key to understanding modern Russian history is the question of whether Russia is allowed in its development, does it appeal to Western values ​​and ideological schemes, or does it try to search specifically Russian ways of civilizational development. The conflict between these two orientations is far from over decided and with the passage of time it seems that in the foreseeable future it will not even be clearly resolved in favor of one of the two options. Modern and democratic Russia meet and will meet the Russia of old instincts and phobias. In Russia conservative and overlooked the needs of the individual strengthen the influence of social groups based on other, more European ones standards and values. Proponents of these orientations were called at another time and on another occasion Westerners and Slavophiles. Today we could name these two groups as, for example Euro-Atlantists and Eurasians, but the essence of their division remains the same - there is a difference between them dispute over the modernization of Russia.